Preschool and Me: Educational-clinical linkage to improve health equity for children with developmental delays and disabilities from historically marginalized communities - Tina L. Schuh; Kathleen R. Diviak; Sarai Coba-Rodriguez; Emily Pela; Raphael Kinney; Michael L. Berbaum; Amanda Klemas; Kruti Acharya; Molly Martin; Reshma Shah (Contemporary Clinical Trials Communications)
Societal and structural inequities have resulted in longstanding health care disparities among Black, Latino/a/e, and low-income preschool children with developmental delays and disabilities (PCw/DD), depriving them of educational and therapeutic services that improve future academic, economic, and health outcomes. To address this issue, we developed Preschool and Me (PreM), a community-clinical linkage (CCL) implemented within healthcare settings serving historically marginalized communities. This novel CCL, an educational-medical linkage model, aims to increase access to school-based services for PCw/DD. Combining key components of CCLs with a personalized medical-education care plan and remote navigator support, PreM targets multiple levels of influence impacting access to school-based therapeutic and educational services. We will utilize a hybrid effectiveness-implementation approach in two models of real-world service delivery conditions. Participants (n = 320) will be randomized to either 6 months of PreM or a waitlist control arm beginning the intervention after a 6-month delay. Our specific aims are to test the effectiveness of PreM on access to school-based services as well as health service outcomes; examine mediators of intervention effects using a mixed-methods approach; and explore social determinants of health as potential moderators. We will simultaneously conduct an implementation evaluation. The results of this study have the potential to support effective implementation of CCL models within pediatric clinical settings serving historically marginalized communities which can be utilized to improve health outcomes for families and their children with a range of health conditions.